2014
DOI: 10.1128/jvi.01825-14
|View full text |Cite
|
Sign up to set email alerts
|

Novel Denisovan and Neanderthal Retroviruses

Abstract: Following the recent availability of high-coverage genomes for Denisovan and Neanderthal hominids, we conducted a screen for endogenized retroviruses, identifying six novel, previously unreported HERV-K(HML2) elements (HERV-K is human endogenous retrovirus K). These elements are absent from the human genome (hg38) and appear to be unique to archaic hominids. These findings provide further evidence supporting the recent activity of the HERV-K(HML2) group, which has been implicated in human disease. They will al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Eight of our validated loci have been recently reported in the genomes of two sequenced archaic samples (42,51) in addition to modern humans (12). We confirmed an additional three reported "archaic" sites in our data [19p12e and 10q24.2b, respectively: "De11" and "De12" in the study by Agoni et al (42); 19q13.43: "Ne5" in the study by Lee et al (51)], but found no evidence of the remaining eight reported archaic events.…”
Section: Discussionmentioning
confidence: 99%
“…Eight of our validated loci have been recently reported in the genomes of two sequenced archaic samples (42,51) in addition to modern humans (12). We confirmed an additional three reported "archaic" sites in our data [19p12e and 10q24.2b, respectively: "De11" and "De12" in the study by Agoni et al (42); 19q13.43: "Ne5" in the study by Lee et al (51)], but found no evidence of the remaining eight reported archaic events.…”
Section: Discussionmentioning
confidence: 99%
“…A small group of HERVs belonging to ERVK elements was actively proliferating in the genome after the divergence of human and chimpanzee ancestor lineages [19]. Few group members were even specific to non-human hominid genomes of Neanderthals and Denisovans [224]. Human specific HERVs, in turn, are presented by *130-140 members that shaped *330 kb of the human DNA.…”
Section: Impact On Human Evolutionmentioning
confidence: 99%
“…DNA sequences of these extinct hominins and those of present‐day humans share common ancestors on average about 800 000 years ago . Six of the HML‐2 loci identified in these archaic hominins appear to be absent in modern humans , but although highly suggestive, this does not necessarily mean that these retroviruses were still replicating and integrating into our hominin cousins after the presumed population split between modern humans on the one hand and Neanderthals and Denisovans on the other . They might simply be present at low frequencies in modern humans and have escaped discovery or have been completely lost as a result of genetic drift .…”
Section: Inventory Of the Hml‐2 Archivementioning
confidence: 99%